Implementation of Internal Quality Audit at IKesT Muhammadiyah Palembang - Suprianto, Hendra (PPSDP International Journal of Education, 2024)
The Internal Quality Assurance System (SPMI) in universities has an important role in the implementation and improvement of the quality of educational services provided by universities. One of the ways to evaluate the fulfillment of the higher education standards in question is through the Internal Quality Audit (AMI) process. The implementation of AMI at IKesT Muhammadiyah Palembang has been carried out well and has had a positive impact on improving the quality of higher education implementation and has also referred to SPMI and the PPEPP cycle. The Quality Assurance Institute (LPM) reported the results of the AMI training to the Rector of IKesT Muhammadiyah Palembang and invited all leaders of faculties, study programs and work units to present the results of the AMI that had been implemented, with this the rector can know where the weaknesses and shortcomings need to be improved and improved in order to create Good University Governance (GUG).